Structure Of Educational Activity for Learning It Elements Of Primary Class Students - B.E. Sabirov (Periodica Journal, 2024)
This article discusses the structure of educational activities and its organizers for learning the elements of informatics for a primary school student.
Keywords: Informatics; Computer; Algorithm